Classifying dynamic contact line modes in drying drops1. Issue 8 (28th February 2015) - Baldwin, Kyle Anthony; Fairhurst, David John
<x xml:space="preserve">Abstract</x> Evaporating droplets of both PEO polymer solutions and blood at low pressure are observed to form pillar-like deposits when dried. We use normalised h–R plots to illustrate that this behaviour is volume-independent and find scaling arguments to support our measurements that the contact line recedes with a speed inversely proportional to the droplet radius.